(untitled) (KULT_online, 2014)
This volume edited by Carsten Meiner and Kristen Veel investigates how catastrophes and crises are processed by the cultures in which they occur. Drawing from many disciplines within the study of culture, the volume groups essays according to the categories of understanding, remembering, imagining, and desiring catastrophes and crises. A wide range of historical events, medial forms, and cultural artifacts enter into the discussion, which makes the book best suited to those seeking an expansive overview of and insight into the diversity of the latest cultural-studies work on the subject.